Manajemen Pengelolaan Properti Syariah pada PT. Khansa Property Syariah Perspektif Fikih Muamalah - Khaerul Aqbar; Iskandar Iskandar; Awal Rifai Wahab; Abdul Aziz Husaini (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2022)
This study aims to know and understand management and the application of sharia property contracts at PT. Khansa Properti Syariah in the perspective of fiqh muamalah. This research is a qualitative field research using a normative juridical approach. Data collection methods used in this study were interviews and documentation. The results of the study show that in management there are three stages, namely planning or marketing, launching or during marketing, and post-marketing. PT. Khansa Property Syariah pays great attention to location determination, pricing, building quality, services, buying and selling transactions, promotional media, and the Islamic environment. The practice of applying the contract of sale and purchase of property by PT. Khansa Property Syariah uses the bay' istiṣnā` contract in the sale and purchase transaction of the property in accordance with the muamalah fiqh perspective because the buyer has the right to discuss the contents of the contract but within the limits given by PT. Khansa Property Sharia. Likewise, management and marketing have fulfilled the terms of sale and purchase and do not conflict with Islamic law according to the perspective of muamalah fiqh. The implications of this research for PT. Hopefully Khansa Properti Syariah in the future will always implement the implementation of buying and selling according to Islamic law. In carrying out the property business, the company should also have large capital even without involving a bank, so that buyers do not have to wait long for their houses to be built.